Extending the range of Plug-in Hybrid Electric Vehicles by CVT transmission optimal management. (October 2018) - Yan, Xingda; Fleming, James; Lot, Roberto
Abstract: Due to the ability to obtain energy from direct connection to the electricity grid, plug-in hybrid electric vehicles benefit both society and drivers environmentally and economically by reducing energy consumption and emissions. To extend the travel range, existing studies focus mostly on optimizing the power split of the internal combustion engine and battery without considering the impact of the transmission system. This paper deals with the optimization of a continuously variable transmission (CVT) operation for a parallel pre-transmission hybrid powertrain. The novelty of this paper is that the operation of both engine and CVT transmission are optimized together, resulting in a better fuel efficiency. Simulation work has been carried out to compare the performance of the optimized CVT transmission with a fixed transmission, showing that the fuel consumption is reduced and hence the range is increased for the optimized CVT, which makes the engine to operate in higher efficiency points. A key advantage of the formulation proposed is that the result of the optimization process may be expressed in terms of a 2D map that for any pair of vehicle speed and traction force gives the optimal value of the CVT transmission ratio. Such a map may be easily implemented in real vehicular applications.